Distinct profiles of functional connectivity density aberrance in Alzheimer's disease and mild cognitive impairment - Miao, Dawei; Zhou, Xiaoguang; Wu, Xiaoyuan; Chen, Chengdong; Tian, Le (Frontiers in Psychiatry, 2022)
Investigating the neuroimaging changes from mild cognitive impairment (MCI) to Alzheimer’s disease (AD) is of great significance. However, the details about the distinct functional characteristics of AD and MCI remain unknown. In this study, we investigate distinct profiles of functional connectivity density (FCD) differences between AD and MCI compared with normal population, aiming to depict the progressive brain changes from MCI to AD. As a data-driven method, FCD measures profiles of functional connectivity for the given voxel at different scales. Resting-state functional magnetic resonance imaging images were obtained from patients with AD, MCI and matched healthy controls (HCs). One-way ANCOVA was used to investigate (global, long-range and local) FCD differences among the 3 groups followed with post hoc analysis controlling age, sex and head motion. The 3 groups exhibited significant global FCD differences in the superior frontal gyrus. The post hoc results further showed that patients with AD had a significant increase in global FCD values than patients with MCI and HCs. Patients with MCI exhibited an increased trend compared with HCs. We further identified brain regions contributing to the observed global FCD differences by conducting seed-based functional connectivity analysis. We identified that the observed global FCD differences were the additive effects of altered functional connectivity between the superior frontal gyrus and posterior default model network. These results depicted the global information communication capability impairment in AD and MCI providing a new insight in to the progressive brain changes from MCI to AD.